The Radioactivity of Shielding Design of a Gamma-Ray Spectroscopy - Ahmed, Ali Hassan (Sulaimani Journal for Pure and Applied Sciences, 2001)
Radioactivity of let ,rd shielding blocks and the Marinelli beaker used with a computerize Gamma- Ray ,spectroscopy were studied. More than twenty Lines were identified and ascribed to radiomuclides of Uranium. Thorium and Actinium natural decay serieses, as well as the 1461 keV y-line due to natural 40K radio muclide was clearly observed. For these runes, both quantitative and qualitative measurements were one among them, four common lines were determined. Because of the low intensity of other y-lines they were ascribed qualitatively_ Furthermore, several fluorescence lines were observed. A good agreement whit standard results ofN,D.S. and other studies is obtained
Keywords: Gamma Ray Spectra copy; NBG Radioactivity